Replacement of Anterior Composite Resin Restorations Using Conservative Ceramics for Occlusal and Periodontal Rehabilitation: An 18-Month Clinical Follow-Up - Leonardo Fernandes da Cunha; Rayane Alexandra Prochnow; Adriana Osten Costacurta; Carla Castiglia Gonzaga; Gisele Maria Correr (Hindawi Limited, 2016)
This case report describes a patient with discolored and fractured composite resin restorations on the anterior teeth in whom substitution was indicated. After wax-up and mock-up, the composite was removed and replaced with minimally invasive ceramic laminates. An established and predictable protocol was performed using resin cement. Minimally invasive ceramic restorations are increasingly being used to replace composite restorations. This treatment improves the occlusal and periodontal aspects during the planning and restorative phases, such as anterior guides, and laterality can be restored easily with ceramic laminates. In addition, the surface smoothness and contour of ceramic restorations do not affect the health of the surrounding periodontal tissues. Here we present the outcome after 18 months of clinical follow-up in a patient in whom composite resin restorations in the anterior teeth were replaced with minimally invasive ceramic laminates.